Prenatal magnetic resonance imaging detection of temporal lobes and hippocampal anomalies in hypochondroplasia. (11th June 2014) - Cesaretti, Claudia; Spaccini, Luigina; Rustico, Mariangela; Parazzini, Cecilia; Doneda, Chiara; Re, Thomas J.; Righini, Andrea
ABSTRACT Hypochondroplasia (HCH) is a genetic skeletal dysplasia, inherited in an autosomal dominant fashion. About 50–70% of HCH patients have a mutation in FGFR3 gene and in the majority of cases it is a de novo mutation. Recent magnetic resonance imaging studies on relative large cohorts of HCH patients have showed a central nervous system involvement with a high incidence of characteristic temporal lobe and hippocampal abnormalities. To the best of our knowledge, this report shows the first magnetic resonance imaging prenatal detection of characteristic brain anomalies in a case of HCH, molecularly confirmed through postnatal FGFR3 analysis. © 2014 John Wiley & Sons, Ltd.